Cardioprotective effects of Moku-boi-to and its impact on AngII-induced cardiomyocyte hypertrophy - Tagashira, Hideaki; Abe, Fumiha; Sato-Numata, Kaori; Aizawa, Karen; Hirasawa, Kei; Kure, Yoshinobu; Iwata, Daiki; Numata, Tomohiro (Frontiers in Cell and Developmental Biology, 2023)
Cardiomyocyte hypertrophy, induced by elevated levels of angiotensin II (AngII), plays a crucial role in cardiovascular diseases. Current therapeutic approaches aim to regress cardiac hypertrophy but have limited efficacy. Widely used Japanese Kampo medicines are highly safe and potential therapeutic agents. This study aims to explore the impact and mechanisms by which Moku-boi-to (MBT), a Japanese Kampo medicine, exerts its potential cardioprotective benefits against AngII-induced cardiomyocyte hypertrophy, bridging the knowledge gap and contributing to the development of novel therapeutic strategies. By evaluating the effects of six Japanese Kampo medicines with known cardiovascular efficiency on AngII-induced cardiomyocyte hypertrophy and cell death, we identified MBT as a promising candidate. MBT exhibited preventive effects against AngII-induced cardiomyocyte hypertrophy, cell death and demonstrated improvements in intracellular Ca2+ signaling regulation, ROS production, and mitochondrial function. Unexpectedly, experiments combining MBT with the AT1 receptor antagonist losartan suggested that MBT may target the AT1 receptor. In an isoproterenol-induced heart failure mouse model, MBT treatment demonstrated significant effects on cardiac function and hypertrophy. These findings highlight the cardioprotective potential of MBT through AT1 receptor-mediated mechanisms, offering valuable insights into its efficacy in alleviating AngII-induced dysfunction in cardiomyocytes. The study suggests that MBT holds promise as a safe and effective prophylactic agent for cardiac hypertrophy, providing a deeper understanding of its mechanisms for cardioprotection against AngII-induced dysfunction.